2019
DOI: 10.3390/jcm8122116
|View full text |Cite
|
Sign up to set email alerts
|

Modern Surgery-First Approach Concept in Cleft-Orthognathic Surgery: A Comparative Cohort Study with 3D Quantitative Analysis of Surgical-Occlusion Setup

Abstract: Despite the evident benefits of the modern surgery-first orthognathic surgery approach (reduced treatment time, efficient tooth decompensation, and early improvement in facial esthetics), the challenge of the surgical-occlusion setup acts as a hindering factor for the widespread and global adoption of this therapeutic modality, especially for the management of cleft-skeletofacial deformity. This is the first study to assess three-dimensional (3D) quantitative data of the surgical-occlusion setup in surgery-fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 62 publications
0
26
0
1
Order By: Relevance
“…Details of the preoperative and postoperative treatments adopted in this center have been previously described [26][27][28][29][30][31][32][33][34]. All included patients underwent the modified surgery-first approach with the 3D computer-aided single-splint two-jaw orthognathic surgery technique (Figure 1).…”
Section: Orthognathic Surgery Treatmentmentioning
confidence: 99%
“…Details of the preoperative and postoperative treatments adopted in this center have been previously described [26][27][28][29][30][31][32][33][34]. All included patients underwent the modified surgery-first approach with the 3D computer-aided single-splint two-jaw orthognathic surgery technique (Figure 1).…”
Section: Orthognathic Surgery Treatmentmentioning
confidence: 99%
“…Since no prior investigation employed the FACE-Q questionnaire and 3D morphometry for analysis of a cohort of patients, we could not perform a direct comparative appraisal of the current versus former findings. The generalizability of our findings cannot be assumed, as all included patients were treated by particular procedural strategies, including the digital occlusion set up, virtual surgery, surgeryfirst model, and two-jaw orthognathic surgery with single-splint technique 3,[45][46][47][48][49] . We enrolled a restricted final sample as only matched patients and controls were included for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…No postoperative intermaxillary fixation was adopted and the orthodontic therapy was initiated 2 to 4 weeks post-operatively. Full descriptions of the standard pre-and post-surgical treatment principles and details used in this center has previously been published 3,[45][46][47][48] . FACE-Q instrument.…”
Section: Skeletofacial Reconstructive Approach All Patients Underwenmentioning
confidence: 99%
“…For both 2D planning and 3D simulation groups, the average follow-up period was longer than 12 months, with the minimum time criteria for acquisition of facial photographic images to mitigate potential problems related to facial soft tissue swelling 43 . The involved patients had differences (mean of 3 months) for postoperative follow up parameter as it was related to the time required for orthodontic adjustment before debonding and it is broadly variable from patient to patient in different cohorts 44,45 . Our findings demonstrated that both groups…”
Section: Discussionmentioning
confidence: 99%